Appropriateness of the use of innovative technologies in the formation of personality oriented motivation of students to physical education - V.A. Gruzhevsky (H.S. Skovoroda Kharkov National Pedagogical University, 2014)
Purpose: introduction in educational process of innovative technologies aimed at creating a student-centered motivation of students on the value of physical education. Material : the study involved 379 1st year students from different regions of the Crimea and the students of the Crimean Tatar nationality. Results : determined the dominant category of motives that emphasize feature innovative technologies in shaping the personality- oriented motivation of students to physical education. Identified the following groups of motives: cognitive activity, social, emotional satisfaction from motives of exercise; motives of needs of importance of physical education in the future professional activity; motives of critical attitude to the conditions and forms of organization of physical education. Found that the fundamental principles in innovative implementations become the following: the humanization; nature- compliance and nature- appropriate; tolerance; differentiation and individuality, which is closely linked with the principles of physical education. Conclusions : the proven efficiency of formation of positive student-centered motivation among college students to physical education provided records of all significant components of the previous ethnic environment.